Analysis of the Needs for Local Culture-Based Mandarin Language Textbooks in Indonesia to Improve the Effectiveness of Language Teaching - Karimah, Icha Fais Nurul (Raja Zulkarnain Education Foundation, 2025)
This study aims to analyze the use of Mandarin language textbooks based on local culture in Indonesia as an effort to enhance the effectiveness of language teaching, as well as to formulate strategies for developing locally relevant textbooks that better meet students' needs. The research involved 120 students and 10 lecturers from the Mandarin Language Education Program in Indonesia, selected purposively. The instruments used in this study included surveys, interviews, and analysis of textbook documents, while data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques based on the Miles and Huberman model, combined with simple descriptive quantitative analysis using SPSS. The results showed that the majority of the courses still used textbooks from China, such as Hanyu Jiaocheng and New Practical Chinese Reader, which, although systematic and in line with HSK standards, were considered less relevant to the socio-cultural context of Indonesian students. Some students had difficulty understanding texts depicting typical Chinese experiences, such as winter or traditional festivals, because these were not aligned with their everyday reality. Based on these findings, the strategies for developing local textbooks include: (1) analysis of students' needs, (2) integration of Indonesian culture into texts and exercises, (3) adjustment of material levels according to HSK standards, and (4) development of materials based on students' real-life experiences. This study concludes that developing culture-based local textbooks is crucial for enhancing the relevance and effectiveness of Mandarin language teaching in Indonesia and strengthening intercultural competence in the learning process.